The palmitoyltransferase Approximated promotes growth via the Hippo pathway by palmitoylation of Fat - Matakatsu, Hitoshi (J Cell Biol, 2017)
The large protocadherin Fat functions to promote Hippo pathway activity in restricting tissue growth. Loss of Fat leads to accumulation of the atypical myosin Dachs at the apical junctional region, which in turn promotes growth by inhibiting Warts. We previously identified Approximated (App), a DHHC domain palmitoyltransferase, as a negative regulator of Fat signaling in growth control. We show here that App promotes growth by palmitoylating the intracellular domain of Fat, and that palmitoylation negatively regulates Fat function. Independently, App also recruits Dachs to the apical junctional region through protein–protein association, thereby stimulating Dachs’s activity in promoting growth. Further, we show that palmitoylation by App functions antagonistically to phosphorylation by Discs-overgrown, which activates Fat. Together, these findings suggest a model in which App promotes Dachs activity by simultaneously repressing Fat via posttranslational modification and recruiting Dachs to the apical junctional region, thereby promoting tissue growth.